2019
DOI: 10.1111/joim.12981
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypercholesterolemia and elevated lipoprotein(a): double heritable risk and new therapeutic opportunities

Abstract: Familial hypercholesterolemia and elevated lipoprotein(a): double heritable risk and new therapeutic opportunities (Review).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 142 publications
2
79
0
3
Order By: Relevance
“…Clinical conditions resulting in raised CV risk are particularly stimulating, in order to improve choices for handling Lp(a) elevations. Familial hypercholesterolemia (FH) and elevated Lp(a) are a double heritable risk [ 8 ], i.e., carriers of a receptor-negative mutation in the low-density lipoprotein receptor (LDLR) gene with high Lp(a) (> 50 mg/dL) show a higher cardiovascular disease (CVD) risk compared to patients with the same mutation and Lp(a) levels < 50 mg/dL [ 9 ]. In suspected FH patients, the proportion of cases explained by biochemical evaluation of Lp(a) is between 5% and 20%.…”
Section: Introduction—an Overviewmentioning
confidence: 99%
“…Clinical conditions resulting in raised CV risk are particularly stimulating, in order to improve choices for handling Lp(a) elevations. Familial hypercholesterolemia (FH) and elevated Lp(a) are a double heritable risk [ 8 ], i.e., carriers of a receptor-negative mutation in the low-density lipoprotein receptor (LDLR) gene with high Lp(a) (> 50 mg/dL) show a higher cardiovascular disease (CVD) risk compared to patients with the same mutation and Lp(a) levels < 50 mg/dL [ 9 ]. In suspected FH patients, the proportion of cases explained by biochemical evaluation of Lp(a) is between 5% and 20%.…”
Section: Introduction—an Overviewmentioning
confidence: 99%
“…8 The independent CVD risk factor lipoprotein (a) is important to take into consideration when discussing treatments available in the near future and risk stratification for hypercholesterolemic patients. 9 In about 60% to 80% of the definite FH cases, a causative mutation can be found in one of the three known genes, but only in about 20% to 30% of possible FH cases. 10,11 Since the unequivocal diagnosis of FH is primarily based on molecular testing, this leaves medical scientists with a conundrum because up to 60% of the clinically diagnosed patients turn out to be nonmutation carriers, that is, with no identified pathogenic sequence variant in one of the above mentioned genes.…”
Section: Introductionmentioning
confidence: 99%
“…An important finding is the association between cytomegalovirus antibodies and atherosclerosis, which in the Atherosclerosis Risk in Communities Study was observed in individuals with high levels of lipoprotein(a) and fibrinogen [5]. Such an association may also apply to FH patients who have, on average, higher lipoprotein(a) levels compared with the general population [6] and, therefore, may have a higher risk of an atherothrombotic event whilst suffering from COVID-19 and even after recovery. The potential synergism between viral infection and the resulting hypercoagulability related to increased lipoprotein(a) levels merits further investigation.…”
mentioning
confidence: 99%